Levers of Control, Budaya Organisasi, dan Inovasi Sebagai Mediasi untuk Meningkatkan Kinerja UMKM Berbasis Online di Wilayah DKI Jakarta - Dahlia, Lely; Novita, Novita; Mauliddina, Adinda; Nadeak, Darwin (Juara: Jurnal Riset Akuntansi, 2024)
This study aims to examine the variables of levers of control, organizational culture, and innovation as a mediator in improving the performance of Online-based MSMEs in the DKI Jakarta area. This study uses a quantitative descriptive approach, with data obtained through field surveys using questionnaires. The respondents of the study are Online-based MSME actors in the DKI Jakarta Region who sell products through marketplaces or social media, with MSME criteria determined based on judgment sampling. The data was analyzed using the partial least square method.  The results showed that the levers of control variable had a positive and significant influence on performance, while the organizational culture variable did not have a significant effect on the performance of Online-based MSMEs. In addition, the levers of control variable had a positive and significant effect on innovation, but the organizational culture variable did not have a significant effect on innovation. Innovation does not mediate the relationship between levers of control and the performance of Online-based MSMEs, but mediates the influence of organizational culture on the performance of Online-based MSMEs, and has a positive and significant effect on the performance of Online-based MSMEs.